2016
DOI: 10.3390/rs8050435
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Satellite Remote Sensing Data on Simulations of Coastal Circulation and Hypoxia on the Louisiana Continental Shelf

Abstract: Abstract:We estimated surface salinity flux and solar penetration from satellite data, and performed model simulations to examine the impact of including the satellite estimates on temperature, salinity, and dissolved oxygen distributions on the Louisiana continental shelf (LCS) near the annual hypoxic zone. Rainfall data from the Tropical Rainfall Measurement Mission (TRMM) were used for the salinity flux, and the diffuse attenuation coefficient (Kd) from Moderate Resolution Imaging Spectroradiometer (MODIS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Setup and validation of the circulation model are described in detail by Hetland and DiMarco [, ]. Satellite‐derived attenuation coefficients for shortwave radiation [ Schaeffer et al ., ; Ko et al ., ] are used to simulate realistic bottom boundary layer thicknesses in the circulation model [ Fennel et al ., ]. The circulation model is coupled with the pelagic N‐cycle model of Fennel et al .…”
Section: Methodsmentioning
confidence: 99%
“…Setup and validation of the circulation model are described in detail by Hetland and DiMarco [, ]. Satellite‐derived attenuation coefficients for shortwave radiation [ Schaeffer et al ., ; Ko et al ., ] are used to simulate realistic bottom boundary layer thicknesses in the circulation model [ Fennel et al ., ]. The circulation model is coupled with the pelagic N‐cycle model of Fennel et al .…”
Section: Methodsmentioning
confidence: 99%
“…The NCOM hydrodynamic model used with CGEM accurately simulates sea surface elevation, salinity, water temperature, and density (sigma‐t) which are key indicators of cross‐shelf circulation (Ko et al, 2016; Lehrter et al, 2013). Because hypoxia is sensitive to rates of vertical mixing, we evaluated the model's ability to reproduce density stratification.…”
Section: Resultsmentioning
confidence: 99%
“…Physical transport and mixing for the model domain (Figure 1) was simulated using the Navy Coastal Ocean Model (NCOM; Martin, 2000) as described in (Fennel et al, 2016; Ko et al, 2016; Lehrter et al, 2013; Lehrter et al, 2017). The model grid has a resolution of 2 × 2 km in the horizontal (surface grid shown in Figure 1) and 20 equally spaced sigma layers for from 5 to 100 m depth with up to 14 hybrid coordinate layers at depths greater than 100 m. The grid was nested within the Intra‐Americas Sea Nowcast/Forecast System (IASNFS) (Ko et al, 2008; Ko & Wang, 2014), covering the Gulf of Mexico and Caribbean Sea which provided physical initial conditions and dynamic boundary forcing conditions on the eastern, southern, and western boundaries of the model grid (Figure 1).…”
Section: Ecosystem Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ko et al [3] demonstrated the impact of including satellite imagery in simulations of coastal circulation and hypoxia. Using TRMM rainfall data to improve surface salinity flux estimates, and the diffuse attenuation coefficient (K d ) from MODIS to improve estimates of solar penetration, they observed model improvements in water-column heat distribution and hypoxia extent, in comparison with in situ observations.…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%